[Corrigendum] Cellular expression profiles of Epstein_Barr virus_transformed B_lymphoblastoid cell lines - Arkom Chaiwongkot; Nakarin Kitkumthorn; Ratakorn Srisuttee; Supranee Buranapraditkun (My University, 2020)
[This corrects the article DOI: 10.3892/br.2020.1350.].
Keywords: Lymphoblast; Viral-associated cancers and disorders